Iron Oxide Encapsulated Gold Colloidal Nanoparticle Via Rapid Sonochemical Method For Mri And Ct Imaging Application - Dheyab, Mohammed Ali (2021)
Core@shell nanoparticles (Fe3O4@Au NPs) have multiple functions obtained in one stable entity and thus have been extensively investigated. Combining Fe3O4 and Au NPs in one core@shell nanostructure is a promising strategy for diagnostic biomedical applications. However, the conventional direct methods for Fe3O4@Au NPs synthesis are laborious and time-consuming. Therefore, this study presents a facile and rapid sonochemical technique of synthesising Fe3O4@Au NPs with excellent physicochemical properties for magnetic resonance imaging (MRI) and computed tomography (CT) scan. The Au shell is coated on Fe3O4 NPs using a Vibra-Cell ultrasonic solid horn with tip size, frequency and power output of ½ inch, 20 kHz and 750 watts, respectively within 10 minutes. The targeted zeta potential of - 46.125 mV was achieved under the optimum conditions of 10 ml of HAuCl4, 30 ml of sodium citrate (SC) and sonication amplitude of 40%, which is consistent (about 99.2%) with the actual average zeta potential (- 45.8 mV). The stability and monodispersing of Fe3O4NPs improved following modification to Fe3O4@Au, as indicated by the increase in zeta potential from - 24.2 mV to - 45.8 mV. The saturation magnetization (Ms) value of Fe3O4 was 54 emu/g, while that of Fe3O4@Au NP is 38 emu/g. In general, the sonochemical method effectively synthesis highly stable and monodisperse Fe3O4@Au NPs with an average size of about 20 nm within 10 minutes.